Fasciculoventricular Pathways Responsible for Ventricular Preexcitation in Patients With Danon Disease. (September 2018) - Liu, Yang; Wang, Feng; Chen, Xin; Liang, Yingcong; Deng, Hai; Liao, Hongtao; Rao, Fang; Wei, Wei; Zhang, Qianhuan; Zhang, Bin; Zhan, Xianzhang; Fang, Xianhong; et al.
Abstract : Supplemental Digital Content is available in the text.